Sustainable Development Goal 11 and a New Urban Agenda for Caribbean Small Island Developing States: Policy, Practice, and Action - Mycoo, Michelle A.; Bharath, Keisha (Frontiers in Sustainable Cities, 2021)
Many Caribbean Small Island Developing States face the daunting task of fulfilling the United Nations Sustainable Development Goals by 2030. As signatories to the United Nations Sustainable Development Goals, their governments committed to embark on a roadmap to achieve sustainable development within this time frame. In this context, Caribbean Small Island Developing States have embraced Sustainable Development Goal 11 in pursuit of creating inclusive, safe, resilient, and sustainable cities as articulated in various governance, spatial, socio-economic, and environmental policies. Notwithstanding this commitment, a tension exists between policy and practice. Several barriers to policy implementation have stymied efforts to make progress in fulfilling Goal 11. Enabling the impact of sound policy through well-informed practice is pivotal, if these states are to make advancements in ensuring that their population has access to basic services and live in safe, resilient, and sustainable cities without leaving any citizen behind. This paper firstly seeks to critically review existing policies and practice that impact on the attainment of Sustainable Development Goal 11. It highlights the drivers of unsustainable urbanization that are undermining progress in achieving this key sustainable development goal. In keeping with the United Nations declaration of a Decade for Action, this paper secondly makes recommendations for action that are fundamental to putting Caribbean Small Island Developing States on a trajectory leading to the fulfillment of Goal 11. It specifically recommends strategic actions within the context of a New Urban Agenda that are relevant to Caribbean Small Island Developing States that are encountering similar challenges. The experience of Trinidad is drawn upon to provide a narrative of gaps between policy and practice, and to distill key actions for attaining SDG 11 by 2030 and beyond.